Planning Commission Programme Evaluation Organization First Meeting of Development Evaluation Advisory Committee (DEAC) - Planning Commission (Planning Commission, 2005)
The Programme Evaluation Organisation was established in October, 1952, as an independent organization, under the general guidance and direction of the Planning Commission with a specific task of evaluating the community development programmes and other Intensive Area Development Schemes The evaluation set up was further strengthened by the development of methods and techniques of evaluation in the First Five Year Plan and setting up of evaluation machineries in the States during Third Plan (1961-66) and Fourth Plan (1969-74). Gradually with the extension of the Plan Programmes/Schemes in a variety of sectors, viz., agriculture, cooperation, rural industries, fisheries, health, family welfare, rural development, rural electrification, public distribution, tribal development, social forestry, etc., the evaluation work undertaken by the PEO was extended to other important Centrally Sponsored Schemes.
Planning Commission Programme Evaluation Organization